An in-depth study into how organisational wellness programmes impact the work-life balance of CPIT's female part-time employees : a thesis presented in partial fulfilment of the requirements for the Masters of Business Studies in Human Resources Management at Massey University, Extramural, New Zealand - Miles, Laura Elizabeth (Massey University, 2013)
The purpose of this research was to gain an in- depth understanding of the organisational wellness programmes that contribute to and impact on the work- life balance of current female, part- time employee’s at Christchurch Polytechnic Institute of Technology (CPIT). The literature review has shown that although there has been extensive research conducted in the areas of work- life balance, organisational wellness programmes, flexible working arrangements and part- time employees, these topics have not been widely researched specifically looking at the impact of these factors on part- time employees. Some of the main literature findings include the idea that an employee’s wellbeing is holistic and because employees spend a lot of time in the workplace, it is important that the organisation recognises this and develops a workplace that contributes to their employee’s wellbeing and happiness. Unfortunately for some employees many organisations do not see employee wellness as a crucial workplace priority but rather as something that is nice to have. It is significant that this study focused on part- time employees, as working part- time has become an international phenomenon, with a substantial increase in the numbers of part-time workers occurring over the last twenty-five years. The methodology that was used for this research was a single organisation case study, which included semi- structured interviews, an analysis on policies and guidelines, and data from previous research. The main findings show that the interviewees use a wide range of organisational wellness programmes and benefits, and these make a positive contribution to their lives, work and their ability to achieve and maintain a work- life balance. They have many different motivations to voluntarily work part- time hours but the most common was the ability to be able to spend time with their families and children. Working part- time allows them to achieve a work- life balance and to spend more time doing things that they enjoy such as hobbies which helps to maintain that balance. This research contributes to the gap in the part- time employee literature and encourages other researchers to pursue further research in this area. It would be beneficial to conduct follow up research with the same group of employees to measure any change in attitude and perception towards their workplace, as it was apparent conducting the interviews that they were starting to realise just how much they value and enjoy their workplace, the benefits, wellness programmes and the ability to work flexibly.
Keywords: Christchurch Polytechnic Institute of Technology; Women employees; Part-time employment; Work-life balance; New Zealand; Christchurch